PENDEKATAN URBAN ACUPUNCTURE MELALUI PROYEK PADEPOKAN SENI SRENGSENG - Juan Felix Harly Helga; Doddy Yuono (Jurusan Arsitektur dan Perencanaan, 2023)
In Jakarta there are zones that have their respective land use functions, such as economic zones, government zones, cultural zones, green zones, etc. However, many people do not know about these zones, such as Jalan Merdeka Gambir as the government zone, and the Cikini area as one of the